(untitled) (Revista científica Olimpia, 2021)
During the pandemic, Physical Education had many complications because it is a practical subject, to the adaptation of active methodologies such as the use and application of virtual resources; They generated that teachers reinvent the subject, to give better learning possibilities, that combat inactivity, the levels of fear and emotional affectations caused by the contagion prevention measures. The objective of this research is to have an educational proposal for the personal and social development of adolescents in the context of the pandemic aligned with the practice of self-defense. A documentary type investigation was used, raised in two phases: the documentary and the presentation of the proposal aligned to the skills with performance criteria of the Sports practice curricular Block of the Superior sublevel and the Baccalaureate level; in which the curricular contents will be graded to the contents of the proposal in the field of the pandemic. It was concluded that the proposal generates social and personal skills in adolescents through the curricular practice of self-defense, because these actions can reduce the levels of depression, stress, anxiety and physical inactivity caused by the pandemic situation.